Is Macronutrients Intake a Challenge for Cardiometabolic Risk in Obese Adolescents? - Vizzuso, Sara (Nutrients, 2020)
(1) Background: Pediatric obesity is an emerging public health issue, mainly related to western diet. A cross-sectional study was conducted to explore the association between macronutrients intake and cardiometabolic risk factors in obese adolescents. (2) Methods: Ninety-three Italian obese adolescents were recruited; anthropometric parameters, body composition, glucose and lipid metabolism profiles were measured. Macronutrients intake was estimated by a software-assisted analysis of a 120-item frequency questionnaire. The association between macronutrients and cardiometabolic risk factors was assessed by bivariate correlation, and multiple regression analysis was used to adjust for confounders such as age and sex. (3) Results: By multiple regression analysis, we found that higher energy and lower carbohydrate intakes predicted higher body mass index (BMI) z-score, p = 0.005, and higher saturated fats intake and higher age predicted higher HOmeostasis Model Assessment of insulin resistance (HOMA-IR) and lower QUantitative Insulin-sensitivity ChecK (QUICK) index, p = 0.001. In addition, a saturated fats intake <7% was associated with normal HOMA-IR, and a higher total fats intake predicted a higher HOMA of percent β-cell function (HOMA-β), p = 0.011. (4) Conclusions: Higher energy intake and lower carbohydrate dietary intake predicted higher BMI z-score after adjustment for age and sex. Higher total and saturated fats dietary intakes predicted insulin resistance, even after adjustment for confounding factors. A dietary pattern including appropriate high-quality carbohydrate and reduced saturated fat intakes could result in reduced cardiometabolic risk in obese adolescents.